Household Food Consumption Patterns Of Daily Workers Release People's Oil Palm Plantations - Muhammad Thamrin; Nursamsi Nursamsi; Umi Fazri (JASc (Journal of Agribusiness Sciences), 2021)
This research aims to find out how the food consumption patterns of households of daily workers off people's palm oil plantations based on income levels in Desa Perdagangan II Kecamatan Bandar Kabupaten Simalungun. The data analysis method used is a quantitative and qualitative descriptive method with a method of tabulation and interpretation of data. The results showed that food consumption patterns in low income groups with total expenditure of Rp 1,098,572 or 94.5% while in the moderate income group with a total expenditure of Rp 1,455,946 or 84.3%. This means that the group of freelance daily workers with low incomes spend more on food consumption while the group with moderate income is more to non-food consumption.